Between theater & anthropology - Schechner, Richard, 1934- (UPCC book collections on Project MUSE., 1985)
For over two decades Richard Schechner has written about the theater in a manner which ignores the dreary convention of drama as literature and which instead draws attention to the physical fact of live performance. In his recent book, Between Theater and Anthropology, Schechner considers live events or aspects of live events which fall outside common Euro-American definitions of dramatic performance and theater. He broadens the idea of 'performance' to include a wide range of social, ritual, and media activities: East Indian ritual dancing, trance-inducing spiritual song, stories on the Six O'clock News, S/M parlors and sideshows, and numerous other paratheatrical events - scripted and un-scripted, ritual and aesthetic, domestic and exotic. The seven essays included in Between Theater and Anthropology do not build upon each other in a progressive fashion: instead they individually explore unorthodox performance modes proposed in the introductory chapter. This first chapter illuminates 'Points of Contact' between the studies of theater and anthropology. Theater people can help anthropologists identify what to look for in a training or performance situation; and anthropologists can help theater people see performances within the context of specific social systems.